A matemática financeira e o software rhaimes. - GOMES, Erica Farias (Universidade Federal do Tocantins, 2023)
In this work we present a research in which shows the Financial Mathematics in the Graduation with use of Software RHAIMES. For this it was carried out in Books, Archives, Works of Conclusion of Course, Sites among others that approached the chosen concepts for the development of the same one. The guiding question of the work was: what possible interweaving of Financial Mathematics, seen in undergraduate degree in Mathematics, with the use of software RHAIMES in the daily of the Professional of Financial Assistant? This question generated the objective of showing if the practices of Financial Assistant with the use of RHAIMES software are interconnected to what one learns of Financial Mathematics in a degree course in Mathematics Degree. The research approach was qualitative with the Mathematical Modeling method. The analysis of the results showed that the practice of the Financial Assistant with the use of the Software is intertwined with the concepts learned in the discipline of Financial Mathematics, which if the professional does not know can bring erroneous understanding of some launches made in the RHAIMES system, which would generate loss to the company. We found that the little differentiation between the language of the Financial Mathematics course in higher education and the daily practices of a Financial Assistant, which would make it possible to plan a class of this discipline with case studies of this profession, giving greater applicability to the concepts seen in undergraduate Degree in Mathematics.